Encrypted smartphone : elliptic curve diffie-hellman 571 - Tay, Mei Yun. (2011)
Short Message Service (SMS) application has been widely used by majority of the people all over the world. This application basically sends a message to the recipient within the shortest time. However over the years, sending a pure message may not be as safe as we assumed it would be. Hence in this project, it will examine the various encryption methods used to encrypt the message before sending to the receiver also to decrypt the message when received. There are several methods of cryptography that exist in this world but specifically Elliptic Curve Cryptography has been selected in this project and it will be further explained and elaborated in this report. In this project, the encryption of SMS will be programmed and test on Google Android mobile platform. This report will also cover the methodology used to implement the encryption, integration of the encryption into wavecrypt and modifications done on the graphic user interface to enhance the user-friendliness to the users. The report will also discuss the performance analysis of the project.